(3QSGdI aj GdWH hcdjGJgs
(3ChdgG (B:s
(3GdMeO ddg GdPi hbG ef TGA Yf MVjV GdJTHK HCgOGH Gdbjd hGdbGd hHYO abO bad ef GdHUQI TNU Qhei OaJQ OGQ aJPGcQfG ai GdWH hcdjGJg s
(3BNQgG (B:s
(3hdG NUhUjI dYde GdWH HPdc Hd cd ef CNP GdYde Yf GdSWhQ hEdG agh ai CUd GdegGdc GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B37s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs